Population genetic structures of Eleutheronema tetradactylum (Shaw, 1804) and Eleutheronema rhadinum (Jordan and Evermann, 1902) in Malaysian waters - Wahid, Nurul Atikah (2019)
The four finger threadfin, Eleutheronema tetradactylum (Shaw, 1804) and East Asian four finger threadfin, Eleutheronema rhadinum (Jordan and Everman, 1902) are two species of the Polynemidae family that can be found in Malaysian waters. Common name among local is Senangin. There have been no population genetic studies in both species in Malaysia, which are important to provide genetic information for sustainable fisheries management of the two species. Moreover, both Senangin species are also difficult to distinguish morphologically, thus their taxonomic classification are not fully resolved. Therefore, the aims for this study were to determine the levels of genetic divergences between the two Senangin fishes, and to quantify their population genetic structure by using both mitochondrial DNA and microsatellite markers. Totally 151 samples of Senangin were collected from six location around Malaysian coastal water. Samples were obtained from commercial fishing activities. Among 151 individuals, 20 distinct haplotypes were defined. The phylogenetic tree (maximum likelihood) showed two genealogical branches were recognized among the haplotype, this also proven in pairwise distance among the haplotypes. Level of genetic divergence was substantially high (15-17%) supported their taxonomic status as distinct species. The nucleotide diversity was low in E. tetradactylum and E. rhadinum. Both species show the sharing of haplotypes between different populations and this support that both species had a historically widespread natural distribution in the region in the past. Microsatellites analyses for E. tetradactylum also indicated low levels of genetic variation and high degree of population structure among the E. tetradactylum populations. The average observed heterozygosity (HO = 0.5191) obtained was lower than the standard heterozygosity found in most marine populations (HO = 0.79). Through assignment test all samples were assigned to their respective populations. The low genetic variation in both of mitochondrial DNA and microsatellite proved the evidence of over-exploitation of E. tetradactylum in Malaysia. In conclusion, the present study was able to differentiate between E. tetradactylum and E. rhadinum using mitochondrial gene, Cytochrome Oxidase I. The levels of genetic differentiation and population structure between the two species were successfully quantified.